WUJUD KEBUDAYAAN JAWA DALAM BENTUK RUMAH LIMASAN - Kristiana Rizqi Rohmah (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
This research discusses the limas house of Javanese society. One of the Javanese traditional houses. The purpose of this research is to describe the Javanese people's view of life towards the limasan house shape, to describe the Javanese norms towards the limasan house shape, to describe the harmonization principle of Javanese society towards the limasan house shape, to describe the Javanese people's respect for the limasan house shape, to describe the physical dimensions. Javanese society towards the shape of the limasan house, describes the metaphysical dimension of the Javanese society towards the shape of the limasan house. The research method uses descriptive qualitative research with data collection techniques in the form of observation. The results of the research on the Limasan traditional house building based on the Javanese view of life based on their beliefs can be seen from the Javanese house buildings in the Yogyakarta and Surakarta areas which are close to the Keraton that the house building faces south based on the location of Ratu Nyai Roro Kidul. Based on the duality and centrality category of Javanese house buildings. Based on the religious norms adopted by the Javanese, the house buildings are more similar to the Hindu religious buildings, although not all Javanese people embrace the Hindu and Buddhist religions. The form of the building which is simple and has similarities between one house and another is a symbol that the Javanese people uphold the value of harmony. The construction of the Limasan house is based on the principle of respect for the Javanese people which is shown from the front of the house which is commonly called the emper. The empire in the limasan house is made shorter than the first inner building of the limasan house. The simple personality of the people can be seen clearly from the limasan house building. Each part of the house has a metaphysical value which is believed to be the true meaning of the part of the limasan house.